The Problems and Challenges of Infeasible Paths in Static Analysis - Wasef Marashdih, Abdalla; Fitri Zaaba, Zarul; M. Almufti, Saman (International Journal of Engineering and Technology, 2018)
Static analysis is valuable because it imparts the ability to examine all program paths. However, many of these paths are classified as infeasible paths, which signify that these paths will fail to execute. In static analysis, these paths will lead to results that are high false positive. Because static analysis has a vital part in the detection of vulnerabilities and threats in the software as well as in program analysis, improving static analysis is necessary to obtain accurate results and lessen the occurrence of false positive results. Being able to detect infeasible paths is useful in the improvement and development of the results of static analysis. However, the process that is used to identify these infeasible paths is not simple, especially because numerous tools and methods still do not have the efficiency in detecting these kinds of paths within the static analysis. This paper will review the infeasible paths problem in the static analysis, the new methods of solving this problem, and the reassessment of this vital issue in software testing. This paper will also discuss the importance of exposing and getting rid of these paths.Â Â